2019
DOI: 10.1111/1755-0998.13000
|View full text |Cite
|
Sign up to set email alerts
|

A parsimony estimator of the number of populations from a STRUCTURE‐like analysis

Abstract: Population genetics model based Bayesian methods have been proposed and widely applied to making unsupervised inference of population structure from a sample of multilocus genotypes. Usually they provide good estimates of the ancestry (or population membership) of sampled individuals by clustering them probabilistically or proportionally into (anonymous) populations. However, they have difficulties in accurately estimating the number of populations (K) represented by the sampled individuals. This study propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 44 publications
0
64
0
Order By: Relevance
“…Consequently, STRUCTURE analysis together with all the data analysis based on microsatellite markers were performed based on the remaining seven loci and the aggregated Danish samples. The three different approaches implemented in KFinder (Wang, ) to identify the individuals' ancestry from the STRUCTURE (Pritchard et al, ) results, all returned two populations (best K = 2) as the most probable structure (Table ; Figure ). The structure found was not clear, but inspecting the output files suggested that Denmark and Germany belonged to one population and Russia to another population (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, STRUCTURE analysis together with all the data analysis based on microsatellite markers were performed based on the remaining seven loci and the aggregated Danish samples. The three different approaches implemented in KFinder (Wang, ) to identify the individuals' ancestry from the STRUCTURE (Pritchard et al, ) results, all returned two populations (best K = 2) as the most probable structure (Table ; Figure ). The structure found was not clear, but inspecting the output files suggested that Denmark and Germany belonged to one population and Russia to another population (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“… Three different approaches were applied to interpret the best number of clusters (best K ) obtained from STRUCTURE: the mean likelihood Pr[X|K] that maximize K (Pritchard et al, ), ΔK (the largest rate of change of the log probability given the data) (Evanno et al, ; STRUCTURE HARVESTER (Earl & VonHoldt, )), and the Parsimony Index (KFinder, Wang, ), identifying the K , which repeatedly returns the minimal mean admixture of the sample. K = number of assumed clusters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…the K value that maximises the mean logarithmic posterior probability (ln[X|K]; Pritchard et al, 2000); (b) the rate of change of ln [X|K] among K values (ΔK; Evanno, Regnaut, & Goudet, 2005); and (c) the parsimony index (PI) parameter, which identifies the K that yields the most consistent and minimal average admixture (Wang, 2019).…”
Section: Patterns Of Genetic Variationmentioning
confidence: 99%
“…Extensive simulations showed PI more accurately infers the correct number of genetic clusters under a variety of scenarios, including unbalanced sampling, low numbers of loci, reduced genetic divergence, and inbreeding (Wang, 2019).…”
Section: Patterns Of Genetic Variationmentioning
confidence: 99%